The Oxford Handbook of Africa and Economics 2014
DOI: 10.1093/oxfordhb/9780199687114.013.28
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of African Inequality

Abstract: This paper discusses dimensions of inequality in sub-Saharan Africa and their causes. It starts with a review of the empirical evidence about inequality during the colonial period as well as the post-independence era. Then it discusses the forces that determine inequality change, focusing on factor accumulation and structural change. Next it considers the relationship between inequality and growth, the role of agriculture in the development process, the relationships between ethnicity and social stratification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…This actually is an indication that imports were generating significant jobs in Sub-Saharan Africa in the imports supply chain in the region. This result is congruent with those of Bigsten (2012) and IMF (2013) who found that the SSA countries were importing refined products like petroleum for instance Nigeria that is more expensive than the crude oil that they had exported, and this doesn't generate a lot of revenue needed for job creation, though they benefit from the aspect of comparative advantage and economies of scale. The imports chain as well creates significant number of jobs in the SSA region.…”
Section: Effect Of Economic Sectors On Employment In Sub Saharan Afri...supporting
confidence: 85%
“…This actually is an indication that imports were generating significant jobs in Sub-Saharan Africa in the imports supply chain in the region. This result is congruent with those of Bigsten (2012) and IMF (2013) who found that the SSA countries were importing refined products like petroleum for instance Nigeria that is more expensive than the crude oil that they had exported, and this doesn't generate a lot of revenue needed for job creation, though they benefit from the aspect of comparative advantage and economies of scale. The imports chain as well creates significant number of jobs in the SSA region.…”
Section: Effect Of Economic Sectors On Employment In Sub Saharan Afri...supporting
confidence: 85%